Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531697
|View full text |Cite
|
Sign up to set email alerts
|

Enabling relationship building in tabletop-supported advisory settings

Abstract: Recent research has shown that financial advisory encounters can successfully be supported with IT-artifacts. Tabletop scenarios, for example, can increase the transparency of the advisory process for customers. However, we have also had the experience that the relationship quality as experienced by customers can suffer severely when IT-artifacts are introduced. Based on these experiences, we developed guidelines for both, the artifact-design itself as well as for the environment in order to avoid this effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…Researchers implemented a new system on a large, horizontal tabletop touch screen computer around which advisors and clients could sit and make eye contact ( Figure 1) [38].…”
Section: [Table 1 About Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers implemented a new system on a large, horizontal tabletop touch screen computer around which advisors and clients could sit and make eye contact ( Figure 1) [38].…”
Section: [Table 1 About Here]mentioning
confidence: 99%
“…Clients and users reported deeper satisfaction with the process and outcomes of advisory sessions. [38,57]. None of these insights were obvious when the solution was conceived from the desk chair.…”
Section: [Table 1 About Here]mentioning
confidence: 99%
“…While Schwabe and Nussbaumer (2009) had found significant evidences in 2008 that the banking clients would prefer to include (suitable) IT-support in meetings, most banks regarded their client relationship to be so sensitive that any inclusion of IT would ruin it. While this fear may be appropriate for old-fashioned or poorly designed technologies (Heinrich et al 2014a), simulations presented on tabletop or large tablet computers have shown to improve transparency (Nussbaumer et al 2012), understanding (Bradbury et al 2014), learning (Heinrich et al 2014b), profiling and customer orientation, the advice giving process, documentation and compliance fulfillment. Evidence from research, the opportunities offered by new interactive devices and the expectations from clients have recently woken up banks (Nueesch et al 2014) and the have started to seriously experiment with introducing IT in their advisory sessions.…”
Section: Decision Support For Smart Investment: the Case Of Financialmentioning
confidence: 99%
“…The past DSR activities in our research group often targeted the design of innovative IT artifacts in collaborative work environments like advisory service encounters. Although we (and our research group) published DSR related articles in the past years in the domain of travel agencies [11,12] and the financial industry [13][14][15], we often faced a number of problems during the writing process, which sometimes even hindered the publication of valuable design knowledge. (1) During the course of such a projects, design knowledge exists at various levels of maturity at any given point in time (i.e.…”
Section: Research Question: How Can Early Design Knowledge On Informamentioning
confidence: 99%
“…To demonstrate how the publication schema could be applied in practices, we analyze one of our previous scholarly articles [15] that followed this structure. The article covers the topic of interpersonal relationship building when IT artifacts are collaboratively used in a dyadic setting.…”
Section: Applicationmentioning
confidence: 99%